Analisis Faktor-Faktor Penurunan Angka Kemiskinan di Provinsi Jambi dengan Regresi Linier Berganda: Penelitian - Afif Kurnia Ramadhan; Puspa Hanaya Latifah Erjandsa; Selina Febiyanti Sitorus; Bunga Mardhotillah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Poverty in Indonesia remains a situation that needs attention because although the poverty rate has been gradually declining, it is still a concern for developing countries like Indonesia. One region in Indonesia with a high poverty rate is Jambi. According to BPS, poverty in Jambi reached 279.37 thousand people as of March 2022. The purpose of this scientific paper is to examine the influence of educational facilities and educators, social assistance from the government, and trading activities on reducing the poverty rate in Jambi Province using regression analysis. The data used includes the number of schools, the number of teachers, the number of social assistance recipients, the number of traders, and the number of cooperatives in each sub-district in three areas: Jambi City, Muaro Jambi Regency, and Batang Hari Regency. The type of research being undertaken is quantitative and the research method used is data analysis using multiplr regression analysis. The coefficient of determination for the formed regression model is 86.7%, and the regression model is highly significant simultaneously. Based on the results, 5 factors were tested that have a relationship with the reduction of poverty rates. The most influential factor among these 5 factors is social assistance. This can be seen from the P-Value obtained which is less than 0.05.